Validation of a low-cost laser scanner device for the assessment of three-dimensional facial anatomy in living subjects. Issue 9 (September 2018) - Gibelli, Daniele; Pucciarelli, Valentina; Caplova, Zuzana; Cappella, Annalisa; Dolci, Claudia; Cattaneo, Cristina; Sforza, Chiarella
Abstract: The present study compared the reliability of a low-cost laser scanner device to an already-validated stereophotogrammetric instrument. Fifty volunteers underwent duplicate facial scans through laser scanner and stereophotogrammetry. Intra- and inter-instrument reproducibility of linear distances, angles, facial surface area and volume was verified through the Bland–Altman test and calculation of absolute (TEM) and relative (rTEM) technical errors of measurement; rTEM was then classified as follows: <1% excellent; 1–3.9% very good; 4–6.9% good; 7–9.9% moderate; >10% poor. The scans performed through different devices were registered and superimposed to calculate the root mean square (RMS) (point-to-point) distance between the two surfaces. The same protocol was applied to a mannequin head. In inter-instruments comparison, 12/26 measurements showed a "good" rTEM; 5 were "very good". In intra-instrument comparison, most performances worsened, with only 10 of 26 measurements classified as "good" and "very good". All the measurements made on mannequin scans were at least "good", and 14/26 were "very good". Surface area was "very good" only in intra-instrument comparison; conversely, volumes were poorly repeatable for all the comparisons. On average, RMS point-to-point distances were 0.65 mm (inter-devices comparison), 0.56 mm (mannequin scans), 0.42 mm (intra-device comparison). In conclusion, the low-cost laser scan device can be reliably applied to inanimate objects, but does not meet the standards for three-dimensional facial acquisition on living persons.